Accelerating Students’ Critical Thinking through AI and Supportive Digital Platforms - Septianasari, Lina; Srinawati, Wawat; Fajartriani, Tia; Sofiatin, Sofiatin; Triyanto, Triyanto; Takdir, Muh. (Proceeding International Conference on Religion, Science and Education, 2025)
The aim of this research is to elaborate on the role of AI and supportive digital platforms to enhance students’ critical thinking. We conducted this qualitative research from May to June 2024 at a private university in West Java. Interviews and observation became our instruments to collect the data. Moreover, a descriptive qualitative approach was utilized during the data analysis phase. The findings showed that teacher’s instruction on how to use AI and digital platforms during students’ independent learning could help students to level up their critical thinking in completing the task. It also helped the students to be able to obey academic ethical concerns during their task completion. The use of AI and digital platforms in students’ learning process gave beneficial values for the students. However, the teachers’ role in explaining how to use these tools to elaborate students’ ideas is significantly important to prevent students from breaking academic ethical concerns, like plagiarism and failure in developing their original ideas.